(untitled) (MAUSAM, 1993)
Capability has been developed at the INSAT Meteorological Data Utilisation Centre (MDUC). New Delhi for making sounding retrievals using data from the U.S. Polar Orbiting Satellites; The International TOYS Processing Package (ITPP) developed by the University of Wisconsin, USA, was used for asking temperature soundings software for front-end processing and input of 1000 hPa analysis data Into the retrieval algorithm was developed at MDUC. In the physical retrieval method regression estimates generated listing stratospheric level HIRS channels and MSU channels were used as Initial guess. For the surface, two options were used, (i) climatological guess, and (ii) 1000 hPa analysis. The paper discusses temperature retrievals over the Indian region made on 13 selected dates from different seasons in 1989-91. Results of comparison of satellite retrievals with colocated radiosonde data are presented. There is good agreement between the two from 700 hPa to 150 hPa levels, with RMSE with 3 C. The error is higher at 850 hPa and near the surface, when climatologic IS used as surface guess, but IS within 3°-4° C when the 1000 hPa analysis is used.